A Survey and Critical Evaluation of Isolation, Culture, and Cryopreservation Methods of Human Amniotic Epithelial Cells. Issue 7 (3rd April 2022) - Naeem, Aisha; Gupta, Nikita; Arzoo, Natasha; Naeem, Usra; Khan, Muhammad Jawad; Choudhry, Muhammad Umer; Cui, Wanxing; Albanese, Chris
ABSTRACT: Human amniotic epithelial cells (hAECs), derived from an epithelial cell layer of the human amniotic membrane, possess embryonic stem-like properties and are known to maintain multilineage differentiation potential. Unfortunately, an inability to expand hAECs without significantly compromising their stem cell potency has precluded their widespread use for regenerative therapies. This article critically evaluates the methods used for isolation, expansion, and cryopreservation of hAECs. We assessed the impact of these methods on ex-vivo expansion and stem cell phenotype of hAECs. Moreover, the progress and challenges to optimize clinically suitable culture conditions for an efficient ex-vivo expansion and storage of these cells are highlighted. Additionally, we also reviewed the currently used hAECs isolation and characterization methods employed in clinical trials. Despite the developments made in the last decade, significant challenges still exist to overcome limitations of ex-vivo expansion and retention of stemness of hAECs in both xenogeneic and xenofree culture conditions. Therefore, optimization and standardization of culture conditions for robust ex-vivo maintenance of hAECs without affecting tissue regenerative properties is an absolute requirement for their successful therapeutic manipulation. This review may help the researchers to optimize the methods that support ex-vivo survival, proliferation, and self-renewal properties of the hAECs. Abbreviations: AM: Human amniotic membrane; CM-HBSS: Ca ++ and Mg ++ free HBSS; DMEM: Dulbecco's Modified Eagle Medium; DMEM-HG: DMEM-high glucose; EMEM: Eagle's Modified Essential Medium; EMT: Epithelial-to-mesenchymal transition; EpM: Epi-life complete media; ESC: Embryonic stem cells; ESCM: Epithelial cell surface markers; hAECs: Human amniotic epithelial cells; HLA: Human leukocyte antigen; IM: Immunogenicity markers; iPSC: Induced pluripotent stem cells; KOSR; KSR: Knockout serum replacement; KSI: Key success indicators; CHM: Cell heterogeneity markers; Nanog: NANOG homeobox; Oct-4: Octamer binding transcription factor 4; OR: Operation room; P: Passage; PM: Pluripotency markers; SCM: Stem cell markers for non-differentiated cells; Sox-2: Sry-related HMG box gene 2; SSEA-4: Stage-specific embryonic antigen; TRA: Tumor rejection antigen; UC: Ultra-culture; XF: Xenogeneic free